Relationship between circadian syndrome and stroke: A cross-sectional study of the national health and nutrition examination survey - Wang, Yuling; Yang, Ling; Zhang, Yan; Liu, Junyan (Frontiers in Neurology, 2022)
Aim The aim of this study was to assess the relationship of circadian syndrome and stroke. Methods We performed a cross-sectional analysis of 11,855 participants from the National Health and Nutrition Examination Survey (NHANES) database between 2005 and 2018, and collected the baseline characteristics. Multivariate logistic regression models were developed to explore the association between circadian syndrome and stroke. Simultaneously, subgroup analyses based on the difference of gender, race, and components associated with circadian syndrome also were performed. The odds ratio (OR) and 95% CI were calculated in this study. Results All the participants were divided into the non-stroke group and the stroke group. There were approximately 3.48% patients exclusively with stroke and 19.03% patients exclusively with circadian syndrome in our study. The results suggested that the risk of stroke in patients with circadian syndrome was higher than that in patients without circadian syndrome (OR = 1.322, 95 CI%: 1.020–1.713). Similar associations were found in women with circadian syndrome (OR = 1.515, 95 CI%: 1.086–2.114), non-Hispanic whites with circadian syndrome (OR = 1.544, 95 CI%: 1.124–2.122), participants with circadian syndrome who had elevated waist circumference (OR = 1.395, 95 CI%: 1.070–1.819) or short sleep (OR = 1.763, 95 CI%: 1.033–3.009). Conclusion Circadian syndrome was associated with the risk of stroke. Particularly, we should pay more close attention to the risk of stroke in those populations who were female, non-Hispanic whites, had the symptoms of elevated waist circumference or short sleep.